2014
DOI: 10.1177/2047487314552606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home-based training with telemonitoring guidance in low to moderate risk patients entering cardiac rehabilitation: short-term results of the FIT@Home study

Abstract: This analysis shows that HT with telemonitoring guidance has similar short-term effects on exercise capacity and quality of life as CT in CR patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
202
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(214 citation statements)
references
References 24 publications
3
202
1
8
Order By: Relevance
“…A aderência ao treinamento foi semelhante entre os grupos 15 , no entanto alguns estudos 16,18 indicam que a RC Home-based com orientação por telemonitorização tem efeitos que proporcionam melhor aderência a RC, já Lusignan et al 19 apontam que a telemonitorização aumenta a aderência a medicação.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A aderência ao treinamento foi semelhante entre os grupos 15 , no entanto alguns estudos 16,18 indicam que a RC Home-based com orientação por telemonitorização tem efeitos que proporcionam melhor aderência a RC, já Lusignan et al 19 apontam que a telemonitorização aumenta a aderência a medicação.…”
Section: Discussionunclassified
“…O que se confirmam em por outros estudos que encontraram melhora em no controle de vários fatores de risco para DCV 13,15,17,18 .…”
Section: Discussionunclassified
“…Moreover home-based CR is safe and effective, especially in the area of short-term exercise capacity. 7 Home-based, well-known environment may effectively motivate patients, and simultaneously improve their independence compared with inpatient therapy and care.…”
Section: Current Evidencesmentioning
confidence: 99%
“…1 Current research showed home-based cardiac telerehabilitation as safe and effective in improving short-term exercise capacity, but novel telemonitoring techniques should support also its long-term effects on physical fitness depending on age, gender, etc. 7 Large scale prospective randomized studies should show equal efficacy of the cardiac telerehabilitation compared to the traditional face-to-face rehabilitation programs. Detailed standards and guidelines, useful for compartmental studies purposes, should be developed.…”
Section: Directions Of Further Researchmentioning
confidence: 99%
See 1 more Smart Citation